Transverse Strips Instead of Wearable Laser Lights Alleviate the Sequence Effect Toward a Destination in Parkinson's Disease Patients With Freezing of Gait - Cao, Shan-Shan; Yuan, Xiang-Zhen; Wang, Shu-Hong; Taximaimaiti, Reyisha; Wang, Xiao-Ping (Frontiers in Neurology, 2020)
Background: The sequence effect (SE), referring to step-to-step reduction in amplitude, is considered to lead to freezing of gait (FOG) in Parkinson’s disease (PD). Visual cues may alleviate SE and help reduce freezing episodes. FOG patients show significant SE prior to turning or toward a doorway, but the SE toward a destination has not been clearly studied. Objectives: To examine the SE when approaching a destination in PD patients with FOG, and to further explore the effects of different types of visual cues on destination SE. Methods: Thirty-five PD patients were divided into a freezing (PD+FOG, n=15) group and a non-freezing (PD−FOG, n=20) group. Walking trials were tested under three conditions, including without cues (no-cue condition), with wearable laser lights (laser condition), and with transverse strips placed on the floor (strip condition). Kinematic data were recorded by a portable Inertial Measurement Unit (IMU) system. The destination SE and some key gait parameters were evaluated. Results: The PD+FOG group showed greater destination SE in the no-cue and laser conditions when compared to the PD−FOG group. There were no significant differences in the strip condition when comparing destination SE of the two groups. The destination SE was alleviated only by using the transverse strips on the floor. In contrast, transverse strips and wearable laser lights could increase the step length. Conclusions: The significant destination SE may explain why FOG patients are prone to freezing when heading towards their destination. Visual cues using transverse strips on the floor may be a more effective strategy for FOG rehabilitation in PD patients.